Revolutionizing Indonesia's Sales Cycle From Manual Cash to Seamless Automation - Abidah Garizah Bardina; Nurasik Nurasik (Indonesian Journal of Law and Economics Review, 2024)
This study evaluates the implementation of the Accounting Information System (AIS) in the sales cycle at PT. Perdana Sukses Makmur. Using a descriptive qualitative approach, primary data were collected through interviews with sales and cash receipt staff, while secondary data were gathered from literature reviews. Results indicate that while the AIS effectively supports sales processes, cash receipts are still managed manually, leading to occasional errors. The study highlights the need for further system integration to automate cash receipts and enhance overall efficiency. This research underscores the importance of ongoing AIS improvement to keep pace with technological advancements and business requirements. Highlight: 1. AIS supports sales but manual cash receipts cause inefficiencies.2. Data reveal system errors and highlight process inefficiencies.3. System integration needed to automate cash receipts and boost efficiency. Keywords: Accounting Information System, Sales Cycle, Cash Receipts, System Integration, PT. Perdana Sukses Makmur